Global View of Engineering Geology and the Environment: proceedings of the international symposium and 9th asian regional conference of IAEG, BEIJING, CHINA, 23-25 september 2013 - Wu F. Faquan; Qi S. Shengwen (London, Taylor & Francis, 2013)
Global View of Engineering Geology and the Environment contains selected papers from the International Symposium and 9th Asian Regional Conference of the International Association for Engineering Geology and the Environment (IAEG), Beijing, China, 24.-25 September 2013. The book focusses on six topics: Crustal stability and dynamical geo-hazards; Engineering geology in major construction projects; Urbanization and coastal development; New ideology and technology in engineering geology; Structure and behavior of soil and rock mass, and Geo-hazards in karst and loess areas.Global View of Engineering Geology and the Environment presents the latest research results from scientists, leading engineering and industry researchers, and will be much of interest to academics and professionals involved in engineering geology and the environment and related areas, i.e. soil mechanics, rock mechanics, and hydrogeology.